2007
DOI: 10.1590/s0037-86822007000100017
|View full text |Cite
|
Sign up to set email alerts
|

Prurido do traje de banho: relato de seis casos no Sul do Brasil

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…unguiculata was identified by Silveira and Morandini (1998a, b) (Haddad Jr et al 2001). In that same year, Rossetto et al (2007) observed the first cases of the disease on the north coast of Santa Catarina. This paper presents fourteen cases of the SBE in southern Brazil, and alerts health teams to possible epidemics on the Santa Catarina coast.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…unguiculata was identified by Silveira and Morandini (1998a, b) (Haddad Jr et al 2001). In that same year, Rossetto et al (2007) observed the first cases of the disease on the north coast of Santa Catarina. This paper presents fourteen cases of the SBE in southern Brazil, and alerts health teams to possible epidemics on the Santa Catarina coast.…”
Section: Introductionmentioning
confidence: 89%
“…The authors emphasize that the incidence of dermatitis in Brazil is probably underestimated because many victims do not seek medical attention (Rossetto et al 2007(Rossetto et al , 2009. This is possibly due to high level of spontaneous resolution in two weeks.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The first descriptions of the disease occurred in 1903, in Florida, United States, by an unknown citizen and in 1939, as medical report, by Thomas 9,20,.22 . HADDAD Jr. et al described the first cases of the disease observed in Brazil in 2001 9 and ROSSETTO et al described additional cases in South region in 2007 22 .…”
mentioning
confidence: 99%
“…BLACk et al in 1994 indicated for the first time the planulae larvae of the scyphomedusae Linuche unguiculata as the probable etiologic agent of dermatitis 1 . This small jellyfish, with a size around 1.5 cm in diameter, is common in the waters of the Caribbean (Belize, Cuba, Mexico), Gulf of Mexico and tropical North Atlantic West (Florida, Cuba and Bahamas), with numerous reports of the disease in those regions, which reaches epidemic proportions 9,20,22 . The planulae larvae of Linuche unguiculata measure approximately 0.5 mm and are small enough to pass through the mesh of swimwear 16 .…”
mentioning
confidence: 99%